Neural sensitivity to natural texture statistics in infancy. Issue 7 (22nd July 2018) - Balas, Benjamin; Saville, Alyson; Schmidt, Jamie
Abstract: During infancy, vision becomes tuned to environmental statistics. For example, infant face recognition "narrows" in response to the frequency of face categories in the visual world, inducing out‐group effects that disadvantage other‐race, other‐species, and other‐age face recognition. There are many other low‐level statistical regularities in visual experience that infants may also become tuned to during this period. In particular, natural scenes have lawful properties that adults and children are sensitive to. To what extent do infants become tuned to these regularities during the first year of life? In particular, do infants exhibit evidence of perceptual narrowing that excludes atypical images from fluent processing? We examined this question by measuring 6‐ and 9‐month‐old infants' event‐related potentials (ERPs) to natural and artificial textures created by: (a) Disrupting local statistics via contrast negation, (b) Disrupting global statistics via parametric texture synthesis, or (c) both of these. We predicted that younger infants' would be sensitive to both manipulations of natural appearance, but that older infants might not distinguish between different kinds of atypical images. Instead, we found that sensitivity to synthetic appearance is only evident late in infancy. We discuss what these results imply for our understanding of visual statistical learning in infancy.